Uncovering the role of superplasticizer in developing nano-engineered ultra-high-performance concrete - Wang, Lili; Ma, Yitong; Li, Liangwei (Frontiers in Materials, 2023)
In this study, the effect of superplasticizer (SP) on the fresh and hardened behaviors of ultra high performance concrete (UHPC) and ultra high performance fiber reinforced concrete (UHPFRC) have been investigated systematically aiming to optimize the use of SP. The obtained results indicated that the addition of SP improved the workability of specimens with ultimate-low water to binder (W/B) ratio, while brought benefit in the strength development in UHPC with lower W/B ratio. The novel phenomenon (SP enhance the mechanical properties of UHPC) is due to the fact that SP reduced the water film thickness, enhanced the packing structure, therefore, resulted in an increased compressive strength. For UHFRPC, similar trends can be witnessed regarding the flowability. However, the alternation of the fresh behavior of UHFRPC attributed to the inclusion of SP had an obvious impact on the fiber distribution, which altered the strength development of UHFRPC. This study revealed the peculiar effect of SP on the performance, especially on the strength development, of UHPC and UHFRPC.